(untitled) (Journal of Association of Educational Management and Policy Practitioners, 2026)
Governments owned higher institutions in Nigeria require a significant amount of funds to achieve their goals and objectives. Ethics and values are regarded to be of utmost significance in not only acquisition of higher education but in the achievement of other career goals as well. It is vital for all the members of the educational institutions to generate information in terms of professional ethics on a regular basis which will help to maintain good terms and relationships with others, performing one’s duties in a satisfactory manner and incurring the feeling of job satisfaction and retaining one’s job. However, funds to higher education in Nigeria continue to be inadequate with the attendant effects of negative influences in the school system. This paper takes a review of the funding in higher institutions, ethical principles and higher education, value education in higher institutions, sustainable national development, challenges facing higher education in Nigeria and solution to challenges of funding higher education. Recommendations were made which include: Government should provide adequate funding for higher education for staff development and procurement of facilities in schools, employ more academic staff for quality teaching and production of quality graduates for sustainable development and put up machineries to fight all forms of corruption in higher institutions.